Efforts To Improve Science Learning Outcomes Through Demonstration Learning Models In Class Vi Students Of SDN 019 Tanjung Sawit Tapung District Kampar District - Sriwidayati, Sriwidayati (Jurnal Ilmiah Mandala Education (JIME), 2023)
This research aims to improve the learning achievement of class VI students at State Elementary School 019 Tanjung Sawit through demonstration model learning about the concept of conductors and insulators. The method used in this research is Classroom Action Research (PTK). PTK in this research consists of 5 stages, namely: planning, action, observation, reflection. The research results show: (1) By using demonstration learning, student learning outcomes in each cycle have increased significantly. Student learning outcomes in cycle I was 80 with 95% completeness, cycle II was 86 with 100% completeness. (2) Classical learning in cycle I was 78.61%, increasing to 91.39% in cycle II and group learning from cycle I was 81.25%, increasing significantly in cycle II to 100%.